2018
DOI: 10.1242/dev.171686
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and staging of 3D human retinal organoids across multiple pluripotent stem cell lines

Abstract: Numerous protocols have been described for producing neural retina from human pluripotent stem cells (hPSCs), many of which are based on the culture of 3D organoids. Although nearly all such methods yield at least partial segments of retinal structure with a mature appearance, variabilities exist within and between organoids that can change over a protracted time course of differentiation. Adding to this complexity are potential differences in the composition and configuration of retinal organoids when viewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
322
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(382 citation statements)
references
References 60 publications
20
322
0
Order By: Relevance
“…Despite the ability of these protocols to give rise to laminated retinal organoids, variability in the propensity of iPSCs to give rise to various retinal cell types is often reported. Several groups including ours have reported variable laminar organization between samples differentiated from the same iPSC lines and the presence of non‐neural cell types alongside the retinal structures …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Despite the ability of these protocols to give rise to laminated retinal organoids, variability in the propensity of iPSCs to give rise to various retinal cell types is often reported. Several groups including ours have reported variable laminar organization between samples differentiated from the same iPSC lines and the presence of non‐neural cell types alongside the retinal structures …”
Section: Introductionmentioning
confidence: 85%
“…Several groups including ours have reported variable laminar organization between samples differentiated from the same iPSC lines and the presence of non-neural cell types alongside the retinal structures. 7,11,12 Retinal development in vivo is controlled by a diverse set of signaling pathways and complex interactions between embryological tissues which affect the identity of the resultant cell population.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al , Parfitt et al , Wahlin et al , and others recently described the examples of organoid photoreceptor outer segments. In their studies, the electron microscopy imaging revealed other ultrastructural features of mature photoreceptors, including an outer limiting membrane, inner segments rich in mitochondria, and basal bodies with connecting cilia displaying a photoreceptor‐specific microtubule arrangement.…”
Section: D Retinal Organoids Recapitulate the 3d Histoarchitecture Amentioning
confidence: 99%
“…As previously mentioned, a number of described protocols have permitted the generation of retinal tissue from hPSCs with varying efficiencies allowing us to mimic the early stages of human eye development and to model human retinal disease pathogenesis and repair [15,17,19,[21][22][23][24][25][26][27] (Tables 1 and 2). These stratified structures display some human-specific features: they are larger in size compared with mouse counterparts and contain different retinal structures, including an outer nuclear layer with photoreceptors (rhodopsin+, recoverin+), an inner nuclear layer with horizontal (calbindin+, calretinin−), bipolar (Chx10+, Pax6−), amacrine (Pax6+, calretinin+), Müller glia cells (CRALBP+), and a RGC layer with RGCs (Brn3+, Pax6+, calretinin+) ( Fig.…”
Section: D Retinal Organoids Recapitulate the 3d Histoarchitecture Amentioning
confidence: 99%
“…The pioneering work of the Sasai laboratory has uncovered these astonishing properties of pluripotent cells . Although culturing retinal organoids consumes substantial amount of time up to 150 days, several laboratories have successfully generated optic cups or retinal organoids harboring retinal pigment epithelia and functional photoreceptors …”
Section: Region‐specific 3d Brain Organoidsmentioning
confidence: 99%